Extraction, GC-MS analysis, cytotoxic, anti-inflammatory and anticancer potential of Cannabis sativa female flower; in vitro, in vivo and in silico - Safir, Waqas; Malik, Arif; Saadia, Haleema; Zahid, Ayesha; Li, Jinyao (Frontiers in Pharmacology, 2025)
This work examines the anticancer activity, the anti-inflammatory nature, and the cytotoxicity of the ethanol extract obtained from the female flowers of Cannabis sativa L using molecular methods in vitro, animal testing in vivo, as well as computational methods and simulations in silico. From the GC-MS analysis, the following bioactive compounds were found: cannabidiol (CBD), tetrahydrocannabinol (THC), and humulene. The antiproliferative activities of the extract were determined on HeLa cells by using MTT, Crystal Violet, and Trypan Blue assays with an IC50 value suggesting 51%-77.6% lethality. The bioinformatics analysis of molecular docking proved significant ligand-protein interactions of CBD, THC, and humulene with cancer-associated proteins such as PD-1/PD-L1, TNF-α, and MMP-9. In vivo, breast cancer was first established in female Sprague-Dawley rats with 7,12-dimethylbenz(a)anthracene (DMBA) then treated with cannabinoids either singularly or in combination. Detailed treatment demonstrated that the use of the three cannabinoids simultaneously yielded the best anticancer and anti-inflammatory outcomes together with the best tumor reduction. The concentration of serum biomarkers of inflammation and tumor progression was substantially reduced in treated groups compared to the control group, which proves the synergistic effects of these cannabinoids in breast cancer therapy. This study emphasizes the importance of medical Cannabis sativa derivatives in cancer treatment.